The context of inter-governmental relations in Zimbabwe reflections from the constitution of Zimbabwe amendment number 20 of 2013 - Chakunda, Vincent (International Organization Of Scientific Research, 2020)
Zimbabwe is politically and constitutionally a unitary, democratic and sovereign state with a three tier governmental structure: national government; provincial and metropolitan councils, and local government (rural district councils and various types of urban councils) according to the Constitution [Amendment No. 20] of 2013. This paper explores the composition, structure and the legal basis of the three tiers of government. Diagrammatic illustrations were used to depict these tiers more elaborately, highlighting focal points of power, authority, accountability and responsibility and how the system is synergised and synchronised from the national to the lower levels. Brief historical reviews are additionally used to locate the transformation of these structures through the vicissitudes of colonial discriminatory and racist structures to post independent African government supposedly modelled to dismantle the colonial system with fair, impartial and equitable structures established on the basis of human rights, improved access for all with important non racist, non ethnic codes and disregarding colour or creed.